The More-or-Less Morphing Face Illusion: A Case of Fixation-Dependent Modulation. (September 2014) - van Lier, Rob; Koning, Arno
A visual illusion is presented in which the perceived changes in a morphing sequence depend on eye movements. The phenomenon is illustrated using face morphs: When tracking a moving dot superimposed on a face morphing sequence, the changes in the morphing sequence seem rather small, but when the dot stops moving, the perceived extent of morphing suddenly becomes much larger. We explore this phenomenon further and discuss the observed effects.